Питирим Сорокинлысь «A long Journey» небöг комиöдöмын шыбöльяс - Цыпанов, Йöлгинь (2021)
In modern linguistics, a branch of linguistics - translation studies - was formed, which aims at comprehensive study of the processes of translation from one language to other languages from different aspects. Based on the material of the Russian Finno-Ugric languages, this branch of science takes its first steps. The purpose of this paper is to consider lexical and semantic language errors in the text of the translation of P.A. Sorokin's autobiography into the Komi language, identified by systematic comparisons of text fragments in English, Russian and Komi. The material of the study was the texts of P. A. Sorokin's autobiography published in separate books in different years of publication. The language errors found in the text of the translation of the autobiography of the world-famous sociologist, a native of the Komi region, Pitirim A. Sorokin into the Komi language, published as a separate book in Syktyvkar in 2013, are considered for the first time. The errors considered are analyzed on the basis of subsequent comparisons with the English-language original and the translation of the same book into Russian, published in Syktyvkar in 1991. Analysis of the Komi language of the book (the first 40 pages of his autobiography) allowed to conclude that the translation into the Komi language was made not from the language of the original, as recorded in the bibliographic description, but from the Russian translation of the autobiography, as most translation errors from the Russian-language text moved to the Komi-language one.